2015
DOI: 10.1186/s12906-015-0888-9
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian red propolis: phytochemical screening, antioxidant activity and effect against cancer cells

Abstract: BackgroundThe implementation of new public healthcare models that stimulate the use of natural products from traditional medicine, as a so-called integrated medicine, refers to an approach that use best of both conventional medicine and traditional medicine. Propolis is a widely used natural product by different ancient cultures and known to exhibit biological activities beneficial for health. The large number of studies conducted with propolis had shown that its chemical composition differs as a function of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
1
24

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 45 publications
6
89
1
24
Order By: Relevance
“…However, p ‐coumaric acid was only detected in samples from DER. This phenolic acid, which is not present in our sample collected in Alagoas, along with it caffeic acid, quercetin and luteolin were previously reported in other samples of red propolis from Alagoas and Pernambuco . Chlorogenic acid, ellagic acid and apigenin were also reported in red propolis from Pernambuco .…”
Section: Discussionsupporting
confidence: 76%
“…However, p ‐coumaric acid was only detected in samples from DER. This phenolic acid, which is not present in our sample collected in Alagoas, along with it caffeic acid, quercetin and luteolin were previously reported in other samples of red propolis from Alagoas and Pernambuco . Chlorogenic acid, ellagic acid and apigenin were also reported in red propolis from Pernambuco .…”
Section: Discussionsupporting
confidence: 76%
“…The cytotoxic effects of BRP crude extract are supported by other authors in several types of cancer cells such as cervical (IC 50 of 7.45 μg/ml; Alencar et al, 2007); glioblastoma (IC 50 of 34.27 μg/ml); ovary (IC 50 of 28.76 μg/ml); colon (IC 50 of 25.26 μg/ml; de Mendonça et al, 2015); and pancreas (IC 50 of 10 μg/mL; Awale et al, 2008).…”
Section: Resultssupporting
confidence: 56%
“…The cytotoxic effects of BRP crude extract are supported by other authors in several types of cancer cells such as cervical (IC 50 of 7.45 μg/ml; Alencar et al, ); glioblastoma (IC 50 of 34.27 μg/ml); ovary (IC 50 of 28.76 μg/ml); colon (IC 50 of 25.26 μg/ml; de Mendonça et al, ); and pancreas (IC 50 of 10 μg/mL; Awale et al, ). Vestitol was also tested, being effective at 50 μM against human pancreatic cancer cells by eliminating this cell tolerance against nutrient starvation (Awale et al, ), and showed selective cytotoxicity on leukaemia cells (IC 50 from 2 to 7 μM; Shults et al, ).…”
Section: Resultsmentioning
confidence: 60%
“…The extract was produced by maceration based on literature. 27 To this end, 50 g of propolis had coarsely ground, 200 mL of ethyl alcohol (80 GL) was added via absolute ethyl alcohol, and dropped for 48 hr under resting and light polishing, repeating the process three times. The extracted liquid was concentrated in an evaporator route IKA ® RV10 to 50 C and resuspended in a concentration of 2.5 × 10 4 μgÁmL −1.14…”
Section: Preparation Of Propolis Hydroalcoholic Extractmentioning
confidence: 99%